Wellbore stability analysis of fractured formations based on Hoek-Brown failure criterion. (2018) - Ma, Tianshou; Yang, Zixin; Chen, Ping
The borehole stability is a key factor to ensure the success of drilling in deep fractured formations. However, the analysis method of wellbore stability, which is based on the single plane of weakness theory, is difficult to apply in actual engineering due to the difficulty in determining the occurrence and mechanical parameters of weak planes. Thus, an analytical method was proposed using the Hoek-Brown (H-B) criterion to predict the wellbore stability for fractured formations. The effects of the pore pressure propagation, in-situ stress, and wellbore pressure had been involved. The results show that the critical mud weight (CMW) calculated using H-B criterion is higher than the Mohr-Coulomb. The stability of the borehole in case 3 (reverse faulting) was poorer than case 1 (normal faulting) and case 2 (strike-slip faulting). The unstable zones and CMW gradually increase with time, due to the increase in pore pressure. The filter cake, which has low permeability, plays an important role in maintaining the stability of the wellbore in fractured formations. This method could help to improve the evaluation of wellbore stability for fractured formations. [Received: February 14, 2015; Accepted: May 3, 2016]